Stem cells and stroke—how glowing neurons illuminate new paths. Issue 1 (1st January 2017) - Mitrečić, Dinko; Alić, Ivan; Gorup, Dunja
ABSTRACT: A reliable method of cell tracing is essential in evaluating potential therapeutic procedures based on stem cell transplantation. Here we present data collected using neural stem cells isolated from a transgenic mouse line Thy1-YFP. When transplanted into a stroke affected brain these cells give rise to neurons that express a fluorescent signal which can be used for their detection and tracing. Observed processes were compared with those taking place during normal embryonic neurogenesis as well as during in vitro differentiation. Since the same neurogenic patterns were observed, we confirm that neural stem cell transplantation fits well into the paradigm of neuronal birth and differentiation.